SPECIFIC CHARACTERISTICS OF USING "KPI" IN HEI (Scientific electronic journal "Labor Economics and Human Capital", 2023)
This article is dedicated to the specific features of using KPI in higher education institutions. KPIs are specific indicators that companies use to measure how well they are achieving their goals and implementing their strategy. Today, in addition to the need to improve the efficiency of higher education institutions, there is an increase in demands placed on students, teachers, researchers and management bodies. In this context, the use of key performance indicators (KPIs) is an important tool in the management of educational institutions.
Keywords: Key performance indicators, strategic goals, efficiency, management.